2021
DOI: 10.1093/noajnl/vdab133
|View full text |Cite
|
Sign up to set email alerts
|

Receptor tyrosine kinases as druggable targets in glioblastoma: Do signaling pathways matter?

Abstract: Glioblastoma (GBM) is the most malignant primary brain tumor without effective therapies. Since bevacizumab was FDA approved for targeting vascular endothelial growth factor receptor 2 (VEGFR2) in adult patients with recurrent GBM, targeted therapy against receptor tyrosine kinases (RTKs) has become a new avenue for GBM therapeutics. In addition to VEGFR, the epidermal growth factor receptor (EGFR), platelet-derived growth factor receptor (PDGFR), hepatocyte growth factor receptor (HGFR/MET), and fibroblast gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 89 publications
(103 reference statements)
1
29
1
6
Order By: Relevance
“…However, the total proportion of mutations in the FGFR family is not negligible (16%). Therefore, pan-FGFR inhibitors might effectively treat GBMs [22][23][24]. The frequency of BRAF mutation in our study is higher than that reported in previous reports because patients must have CGPT to attend a clinical trial using BRAF inhibitors after the detection of BRAF V600E using immunohistochemistry.…”
Section: Discussioncontrasting
confidence: 54%
“…However, the total proportion of mutations in the FGFR family is not negligible (16%). Therefore, pan-FGFR inhibitors might effectively treat GBMs [22][23][24]. The frequency of BRAF mutation in our study is higher than that reported in previous reports because patients must have CGPT to attend a clinical trial using BRAF inhibitors after the detection of BRAF V600E using immunohistochemistry.…”
Section: Discussioncontrasting
confidence: 54%
“…PIK3CA mutation can encode a protein that antagonizes PTEN in the PI3K/Akt pathway [ 114 ]. Researchers have summarized the potential mechanisms for resistance, mainly focusing on targeting RTKs [ 104 , 115 ].…”
Section: Neurotransmitters and Their Activation On Intracellular Sign...mentioning
confidence: 99%
“…In GBM, Fyn was found to be overexpressed in patient samples relative to both normal brain and all other tumors, with varying patterns of expression [ 192 , 203 ]. This kinase has also been shown to be downstream of the commonly mutated RTKs in GBM, such as EGFR, PDGFR, and c-MET [ 144 ]. In addition, genetic and pharmacologic inhibitions of Fyn block EGFR-dependent motility and tumor growth both in vitro and in vivo [ 192 ].…”
Section: Tau In Glioblastomamentioning
confidence: 99%